Research Progress on Bacteriocins Produced by Lactic Acid Bacteria and Their Inhibitory Effect on the Biofilm of Staphylococcus aureus - Xiaoge XUE; Yuanyuan LIU; Lina ZHANG; Rui FAN; Yu XIN; Jiage MA; Wei YU; Libo LIU (Shipin gongye ke-ji)
Staphylococcus aureus (S. aureus) is a Gram-positive opportunistic pathogen that can form biofilm on the surface of food. Its biofilm formation poses a serious threat to food processing and food safety. Bacteriocins are peptides with antimicrobial activity produced by lactic acid bacteria (LAB) during metabolism. They can inhibit a variety of food-borne pathogens and the formation of biofilm. In this paper, the classification, mode of action, and synthesis mechanism under the regulation of quorum sensing of LAB bacteriocins are summarized. Furthermore, the conventional methods to improve the synthesis of LAB bacteriocins are briefly described based on the culture conditions and media components. The inhibition of LAB bacteriocins on the biofilm of S. aureus is systemically reviewed. Moreover, with particular reference to the Agr and LuxS/AI-2 quorum sensing systems, the regulatory mechanisms of S. aureus biofilm formation by LAB bacteriocins are briefly outlined. In addition, the future research direction on the mechanism of inhibition of S. aureus biofilm by LAB bacteriocins is prospected. This is expected to provide a scientific basis for the development and widespread application of LAB bacteriocins as biopreservative agents.